2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31971
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Analysis of Motivation Factors in Senior Capstone Design Courses

Abstract: is a graduate student working on her Ph.D. in Mechanical Engineering at Florida Institute of Technology. Her research focuses on the impact of motivation on performance and persistence in mechanical engineering design courses under the guidance of Dr. Beshoy Morkos. She also serves as a graduate student advisor to senior design teams within the mechanical engineering department. Elisabeth is a member of ASME, ASEE,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our previous research has shown that senior capstone design presentations can be regarded as one such stress-inducing environment for students, with the requirement of biweekly presentations to industry clients and instructors. It has also shown a decrease in presentation anxiety and an increase in performance at the end of the course, inferring the impact of repetition and preparedness garnered throughout the course [44,45]. Incentives can be intrinsic and extrinsic, both considered motivation-specific processes leading to desired behavior/outcome of the task.…”
Section: -2 / Vol 22 June 2022mentioning
confidence: 96%
“…Our previous research has shown that senior capstone design presentations can be regarded as one such stress-inducing environment for students, with the requirement of biweekly presentations to industry clients and instructors. It has also shown a decrease in presentation anxiety and an increase in performance at the end of the course, inferring the impact of repetition and preparedness garnered throughout the course [44,45]. Incentives can be intrinsic and extrinsic, both considered motivation-specific processes leading to desired behavior/outcome of the task.…”
Section: -2 / Vol 22 June 2022mentioning
confidence: 96%
“…The components were created to assess knowledge, comprehension, application, motivation, and success rate among other educational aims. The MSLQ structures used in this study are listed in Table 2, along with the subdivision questions [3], [27], [28]. This MSLQ acts as a guide to pinpoint the source of motivation and how learning strategies are utilized in different contexts, both in terms of content and population; to enhance understanding of motivational constructs; In a class like this, I prefer course material that challenges me so I can learn new things.…”
Section: The Pre-and Posttest Questionnairementioning
confidence: 99%
“…When incorporating these high impact experiences into a curriculum, research has also shown that internships that directly relate to the academic program provide higher internship satisfaction and a higher perceived relevance to student's career development [4]. Additionally, when students have a choice in the projects they work on and a genuine interest in the project, the students' performance is impacted by this intrinsic motivation [5].…”
Section: Introductionmentioning
confidence: 99%